Highlighting successes and challenges of the mental health system in Tunisia: an overview of services, facilities, and human resources. (2nd January 2023) - Charfi, Fatma; Ouali, Uta; Spagnolo, Jessica; Belhadj, Ahlem; Nacef, Fethi; Saidi, Olfa; Melki, Wahid
Abstract: Background: Tunisia is a lower-middle-income country located in North Africa with strengths and challenges to its mental health system. Aims: We present an overview of available services, facilities, and human resources to offer mental health care in Tunisia. Methods: We conducted a cross-sectional study, where data for the year 2017 was collected between May 2018 and May 2019 by consulting stakeholders involved in the health field in Tunisia. We compare this information with data published in the WHO-AIMS report (2008), which presents mental health data in Tunisia for the year 2004. Results: Successes of the mental health system in Tunisia include an increase in the ratios of psychiatrists and psychologists, with these ratios being higher than those of other lower-middle-income countries; a flourishing child-psychiatry practice; and an increase in people being treated for mental health conditions. Challenges include psychiatrists being over-represented in large cities along the coastline and in the private sector, and most people receiving treatment in specialized mental health facilities. Conclusions: The further operationalization of the National Strategy for Mental Health Promotion is envisioned, through the training of non-specialists in mental health care and incentives offered to psychiatrists to work in the country's interior and the public sector.